Genocias ir rezistencija Nr. 4(2) - Starkauskas, Juozas; Žemaitienė, Nijolė; Jonušauskas, Laurynas; Sakaitė, Viktorija; Bubnys, Arūnas; Anušauskas, Arvydas; Pocius, Mindaugas (Genocidas ir rezistencija, 1998)
Pilnas leidinys (nuskenuota popierinė versija)